Deep learning an overview - Sukumaran, Asha; Brindha, Thomas (International Journal of Engineering and Technology, 2018)
In recent years, deep learning approaches have gained significant approaches in machine learning. Deep Learning is an accurate and efficient method of recognition and classification. It imitates the working of human brain in processing data. In this paper, we presented a brief over-view of deep machine learning, its architecture and applications.Â